The Human Frontier: Building an Inclusive Organizational Culture - Sanders, Eric J. (Journal of Organizational Psychology, 2017)
Is space really the final frontier, as Star Trek asserts? It seems the final frontier we have been exploring since the dawn of time is understanding ourselves and our relationships with each other. Miller and Katz (2002) say: “The creation of cultures that are truly inclusive provide the possibility of a new vision—a new human frontier.” This article uses material from U.S. pop culture from Star Trek to Woodstock and more to explore how ordinary earthlings in the present time can define, measure and build an inclusive organizational culture.